POLYMORPHISMS IN BETA AND KAPPA-CASEIN ARE NOT ASSOCIATED WITH MILK PRODUCTION IN TWO HIGHLY TECHNIFIED POPULATIONS OF HOLSTEIN CATTLE IN MEXICO - T. Duifhuis-Rivera; C. Lemus-Flores; M. Á. Ayala-Valdovinos; D. R. Sánchez -Chiprés; J. Galindo-García; K. Mejía-Martínez; E. González-Covarrubias (Journal of Animal and Plant Sciences, 2014)
The purpose of this study was to identify genotype variants in the beta-casein (CSN2) and kappa-case (CSN3) genes using the PCR-RFLP method in a population of 202 Holstein cattle from two highly technified farms in the state of Jalisco, Mexico. We further assessed the association of these variants with milk production during a second lactation period. In the first population (n = 102), the genotypic frequencies for CSN2 were A1 = 0.387 and A2 = 0.613, while for CSN3, they were A = 0.829 and B = 0.172. In the second population (n = 100), the genotypic frequencies for CSN2 were A1 = 0.430 and A2 = 0.570, while for CSN3, they were A = 0.795 and B = 0.205. No differences in frequency distribution were noted in either population, and both genes were in Hardy-Weinberg equilibrium. There was greater genetic diversity for the CSN2 gene (0.477 and 0.493) than for the CSN3 gene (0.286 and 0.328) in both populations, with no significant differences between them. The fixation index was low for both genes, suggesting that there was no significant decrease in heterozygosity. The same genetic changes occur in both genes, and give their high similarity index (0.99 and 0.99). The statistical association analysis between genotypes of both genes and milk production revealed there were no significant differences between populations. Furthermore, no significant additive or dominant effects of both casein genes on milk production were identified within our population samples.
Keywords: beta-casein (CSN2); kappa-casein (CSN3); Milk production